2015
DOI: 10.3899/jrheum.140288
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation Syndrome in Patients with Systemic Juvenile Idiopathic Arthritis under Treatment with Tocilizumab

Abstract: These results suggest that the clinical/laboratory features in the course of MAS appear to be similar among patients regardless of whether TCZ is administered. Similarities in the pathophysiological background of MAS and EB-VAHS were also suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 37 publications
(30 reference statements)
1
54
3
1
Order By: Relevance
“…The results we obtained in the current study would indicate there may be a role for tocilizumab in controlling secondary HLH/MAS. Interestingly, a study of tocilizumab for patients with SoJIA observed the appearance of MAS in approximately 4% of the cohort, similar to the reported frequency of MAS found in SoJIA patients not receiving tocilizumab (59,60). Similarly, SoJIA patients treated with other biologic therapies including canakinumab, etanercept, and anakinra showed a low frequency of MAS development while on therapy, indicating that single cytokine inhibition may not be sufficient to prevent the development of MAS.…”
Section: Discussionmentioning
confidence: 62%
“…The results we obtained in the current study would indicate there may be a role for tocilizumab in controlling secondary HLH/MAS. Interestingly, a study of tocilizumab for patients with SoJIA observed the appearance of MAS in approximately 4% of the cohort, similar to the reported frequency of MAS found in SoJIA patients not receiving tocilizumab (59,60). Similarly, SoJIA patients treated with other biologic therapies including canakinumab, etanercept, and anakinra showed a low frequency of MAS development while on therapy, indicating that single cytokine inhibition may not be sufficient to prevent the development of MAS.…”
Section: Discussionmentioning
confidence: 62%
“…An independent adjudication committee examined all cases reported as MAS by investigators, as well as all cases of increased transaminases, in a phase III clinical trial of tocilizumab in sJIA performed in Europe, Australia and the USA (112 patients, 403 patient-years of exposure), in a separate sJIA phase III trial (149 patients, 326 patient-years), and in a post-marketing surveillance program in Japan (366 patients, 524 patient-years) 16,65,66 . In total, 22 events were adjudicated as definite ( n = 11) or potential ( n = 11) MAS in 21 (3.3%) of the 627 patients with sJIA included in the entire database (see Supplementary information S1 (table) for criteria).…”
Section: Effects Of Biologic Therapy On Masmentioning
confidence: 99%
“…Moreover, these episodes also seemed to present less commonly with hepatomegaly. In almost three-quarters of all cases, C-reactive protein (CRP) levels remained within the normal range 16,66 . Given the role of IL-6 in inducing the acute-phase response of the liver, this observation is not unexpected.…”
Section: Effects Of Biologic Therapy On Masmentioning
confidence: 99%
“…One of SJIA complications is Macrophage-Activating Syndrome (MAS), a life threatening disease, associated with impaired bone-marrow and liver functions. Tocilizumab treatment does not prevent or worsen MAS [112]; however, it does mask the clinical symptoms, again by reducing the CRP levels, which allow diagnosing the outbreak of this syndrome [113]. Blocking IL-1 with anakinra, on the other hand, was shown to reduce MAS severity in SJIA patients [114116].…”
Section: Anti-inflammatory Cytokine Biologicsmentioning
confidence: 99%